2010
DOI: 10.1007/s12640-010-9182-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Illness Progression in the Recurrent Affective Disorders

Abstract: Along with genetic vulnerability, multiple environmental factors convey liability to illness progression, including: (1) distal and proximal stressors; (2) recurrence of episodes; and (3) comorbid cocaine abuse. Recurrence of each of these can increase responsivity (sensitize) to themselves and cross-sensitize to the two other factors and drive illness progression as seen clinically in increases in cycle acceleration, severity or duration of episodes, treatment refractoriness, disability, cognitive dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…This theory holds that, analogous to the relationship between kindling and convulsions, some stressors may produce increasing effects over time, which culminate in a full-blown affective episode (Post, 2007, 2010). For example, the more often unipolar or bipolar episodes occur, the more vulnerable one is to recurrences and the development of cognitive dysfunction (Post et al, 2012).…”
Section: Kindling (Neuroplasticity/neurogenesis) Hypothesismentioning
confidence: 99%
“…This theory holds that, analogous to the relationship between kindling and convulsions, some stressors may produce increasing effects over time, which culminate in a full-blown affective episode (Post, 2007, 2010). For example, the more often unipolar or bipolar episodes occur, the more vulnerable one is to recurrences and the development of cognitive dysfunction (Post et al, 2012).…”
Section: Kindling (Neuroplasticity/neurogenesis) Hypothesismentioning
confidence: 99%
“…Up to n, 5 major staging models have been proposed for BD (Berk et al, 2007a, 2007b; Kapczinski et al, 2009; Post, 2010; Post et al, 2012; Cosci and Fava, 2013; Frank et al, 2014). Although there is some support for the proposed staging models, the research base is thin, the heterogeneity of the data is significant, and the studies include small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sensitization between different kinds of stressors is possible [11]. For example, previous studies in rats showed that an inflammatory challenge potentiates a later response to psychosocial stress [12,13].…”
Section: Introductionmentioning
confidence: 99%